2015
DOI: 10.1038/cdd.2015.108
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-independent requirements of steroid receptors EcR and USP for cell survival

Abstract: The active form of the Drosophila steroid hormone ecdysone, 20-hydroxyecdysone (20E), binds the heterodimer EcR/USP nuclear receptor to regulate target genes that elicit proliferation, cell death and differentiation during insect development. Although the 20E effects are relatively well known, the physiological relevance of its receptors remains poorly understood. We show here that the prothoracic gland (PG), the major steroid-producing organ of insect larvae, requires EcR and USP to survive in a critical peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…This gene is thought to be specifically expressed in neurosecretory cells of the prothoracic gland (PG). However, we recently showed that the phm-Gal4 driver is expressed in margin cells of the wing disc [33]. The G-TRACE experiments confirm that cells in third instar larvae activate the phm enhancer in the PG and in the wing disc (figure 5 a – d ).…”
Section: Resultsmentioning
confidence: 56%
“…This gene is thought to be specifically expressed in neurosecretory cells of the prothoracic gland (PG). However, we recently showed that the phm-Gal4 driver is expressed in margin cells of the wing disc [33]. The G-TRACE experiments confirm that cells in third instar larvae activate the phm enhancer in the PG and in the wing disc (figure 5 a – d ).…”
Section: Resultsmentioning
confidence: 56%
“…In D. melanogaster , a dominant‐negative mutation of EcR in the PG of larvae leads to reduced transcript levels of phm , dib and sad and lowers ecdysteroid biosynthesis (Moeller et al , ). Moreover, EcR is required for the survival of PG cells during metamorphosis via an ecdysone‐independent pathway (Mansilla et al , ). Furthermore, knockdown of EcR lowers circulating ecdysteroid levels in a hemimetabolan B. germanica (Cruz et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…First, RNAi of USP in non‐drosophilid insects (Martin et al , ; Tan and Palli, ; Cao et al , ; Lenaerts et al , ; Xu et al , ) causes arrest in development, similar to D. melanogaster (Oro et al , ). Since reduction of USP in the PG cells also causes cell death, prevents ecdysone production and brings about the developmental arrest at late ultimate larval instar in D. melanogaster (Mansilla et al , ), an interesting question then rises: Do the developmental arrests in USP RNAi non‐drosophilid insects result from, at least partially, deficiency of 20E?…”
Section: Introductionmentioning
confidence: 99%
“…EcR and usp also function in the development of male-specific neuronal architecture and male-mating behaviors [65]. More recently, usp and EcR have been shown to be required for the survival of prothoracic gland cells during metamorphosis via an ecdysone-independent pathway [66]. …”
Section: Ecr/lxr/fxr (Nr1h)mentioning
confidence: 99%